Hubungan Hasil Dipstik Urin (Leukosit Esterase, Nitrit dan Glukosuria) dengan Kejadian ISK pada Pegawai - Tuntun, Maria; Aminah, Siti (Jurnal Kesehatan, 2021)
A urine test with a dipstick is an alternative test for rapid leukocyte and bacterial tests to support the diagnosis of urinary tract infection (UTI). The purpose of this study was to determine the relationship between the results of the dipstick test (leukocyte esterase, nitrite, and glucosuria) with the incidence of UTI. The research is observational analytic with a cross-sectional design, which was conducted in September-October 2020, at Campus "X". The population is 351 people, with 92 respondents. A urine test was performed with a dipstick and culture. The dipstick test is a screening step, while the culture is used to confirm the microbiological diagnosis of UTI. The results of the study using the dipstick test showed that 17 people (18,48%) were positive for leukocyte esterase, 27 people (29,35%) were positive for nitrite, and 7 people (7,61%) were positive for glucosuria (DM). The results of the urine culture test showed that 20 people (21,74%) had UTI, which consisted of 11 women and 9 men. There is a relationship between leukocyte esterase and nitrite on UTI (p-value 0.00), but there is no relationship between glucosuria and UTI (p-value 0,279). The use of the dipstick test as a screening test for the incidence of UTI has been used, but it is still necessary to continue with a culture test to be able to make a diagnosis of UTI.